2015
DOI: 10.1016/j.jbiotec.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

A 3D tension bioreactor platform to study the interplay between ECM stiffness and tumor phenotype

Abstract: Extracellular matrix (ECM) structure, composition, and stiffness have profound effects on tissue development and pathologies such as cardiovascular disease and cancer. Accordingly, a variety of synthetic hydrogel systems have been designed to study the impact of ECM composition, density, mechanics, and topography on cell and tissue phenotype. However, these synthetic systems fail to accurately recapitulate the biological properties and structure of the native tissue ECM. Natural three dimensional (3D) ECM hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 23 publications
3
83
0
Order By: Relevance
“…Such attempts have been initiated and it was discovered, for example, that the differentiation of mammary cells in 3D depends on the stiffness of the environment (Alcaraz et al, 2008;Cassereau et al, 2015). The predilection of most organoids for Matrigel is a hurdle, but moving away from Matrigel to hydrogels, where the mechanical properties can be manipulated independently of biochemical components, will empower such approaches (Gjorevski et al, 2016;Greggio et al, 2013).…”
Section: Models With No Gridmentioning
confidence: 99%
See 1 more Smart Citation
“…Such attempts have been initiated and it was discovered, for example, that the differentiation of mammary cells in 3D depends on the stiffness of the environment (Alcaraz et al, 2008;Cassereau et al, 2015). The predilection of most organoids for Matrigel is a hurdle, but moving away from Matrigel to hydrogels, where the mechanical properties can be manipulated independently of biochemical components, will empower such approaches (Gjorevski et al, 2016;Greggio et al, 2013).…”
Section: Models With No Gridmentioning
confidence: 99%
“…In this context, intestinal organoids embedded in bovine collagen gels or elastin domain-based engineered hydrogels with varying stiffness grow with various efficiencies (DiMarco et al, 2014(DiMarco et al, , 2015. Collagen gels loaded with polydimethylsiloxane (PDMS) further enable one to control stiffness independently of pore size (Cassereau et al, 2015).…”
Section: Models With No Gridmentioning
confidence: 99%
“…81,82 For cancer cells, the stiffness of their surrounding ECM can influence metastasis, invasion, proliferation, and chemoresistance. [83][84][85][86] Numerous studies have proven that stiffer substrates enhance the metastatic phenotypes of cancer cells. [87][88][89][90][91] However, within the field of ovarian cancer, studies have resulted in contradictory findings.…”
Section: Ecm Stiffness Within the Ovarian Cancer Mechanical Microementioning
confidence: 99%
“…By using glutaraldehyde as a crosslinker to increase the stiffness of collagen gels independently from pore size or collagen concentration, Lang et al showed that 3D invasion is dependent on pore size; while increased matrix stiffness promotes 3D invasion in gels with large pores (small steric hindrance), increased matrix stiffness hinders cell invasion in gels with small pores (large steric hindrance) [79]. In another interesting study, the Weaver group reported the development of a 3D tension bioreactor platform to facilitate studies on ECM stiffness; by mechanically loading collagen gels to induce gel stiffening (via collagen strain hardening) while maintaining composition and pore size, increasing matrix stiffness was also found to enhance tumor cell invasion [80]. …”
Section: Modeling the Complex Tumor Microenvironment In 3dmentioning
confidence: 99%